Comparative electrocardiographic analysis of midventricular and typical takotsubo syndrome - Padilla-Lopez, Mireia; Duran-Cambra, Albert; Belmar-Cliville, David; Soriano-Amores, Marc; Arakama-Goikoetxea, Sabiñe; Vila-Perales, Montserrat; Bragagnini, Walter; Rodríguez-Sotelo, Laura; Peña-Ortega, Pedro; Sánchez-Vega, Jesús; Carreras-Mora, Jose; Sionis, Alessandro (Frontiers in Cardiovascular Medicine, 2023)
Introduction Takotsubo syndrome (TTS) encompasses distinct variants, with midventricular (MV) as the most common atypical subtype. While electrocardiogram (ECG) abnormalities are well documented in typical TTS, they are less explored in MV-TTS. Methods A retrospective case-control study was conducted where ECGs were reviewed at three time points from symptom onset (within the first 12 h, at 48 h, and at 5–7 days) and compared between patients with typical TTS (n = 33) and those with MV-TTS (n = 27), as classified by ventriculography. Results 12-h ECG findings revealed that typical TTS featured ST-segment elevation through anterior leads V3–V6, with maximal deviation in V3 (0.98 ± 0.99 mm) and V4 (0.91 ± 0.91 mm), whereas MV-TTS featured ST-segment depression in inferior leads (−0.24 ± 0.57 mm in II, −0.30 ± 0.52 mm in III, and −0.32 ± 0.47 mm in aVF) and in precordial leads V4–V6. In 48-h ECG findings, the most significant change was T wave inversion, which was more widespread and deeper in typical TTS, with the most pronounced negative T wave depths, exceeding 3 mm, observed in leads V3–V5; in contrast, in MV-TTS, T wave inversion was evident in fewer leads and showed less depth, with the most pronounced negative T waves reaching 1 mm at most in leads I, aVL, and V2. While the QTc interval was prolonged in both groups at 48 h, this prolongation was more pronounced in typical TTS than in MV-TTS (523 ± 52 ms vs. 487 ± 66 ms; p = 0.029). In ECGs at 5–7 days, results essentially returned to baseline. Conclusion Patients with MV-TTS exhibited a distinctive pattern of ECG abnormalities, marked by ST-segment depression in inferolateral leads, less profound and less extensive T wave inversion that mostly affected leads I, aVL and V2, and attenuated QT interval prolongation compared to typical TTS.